Universal Social Culture: An Empirico-Revelational Paradigm of Shah Wali Allah (American Journal of Islam and Society, 1994)
Shah Wali Allah's (1703-63) ideas and profound intellectual legacycontinue to atrract scholastic interest. Despite many works on his legacy,significant facets remain unknown. As his futuristic ideas hold great promisefor modem and future Islamic thought, his works should be analyzed.We will focus on one such idea: his synthesis of reason, revelation,and empiricism. Building on evidence from an inductive survey of socialphenomena to support the claims of revelation and staying within thedoctrinal framework of revealed guidance, he constructs a universal socialcultute paradigm and says that all Qur'anic injunctions and instructionsof the Prophet are compatible with the demands of human nature.His view of the individual and human society is an integral facet ofhis philosophy of life and is one of the most original parts of his legacy.He sees life as a display of the grand divine scheme in natural order andSocial organization. Although his exposition of humanity's social developmentseems to be in the nature of a humanist and sometimes assumes theform of an empirical survey, his final conclusions confirm the fundamentalpostulates of religion. Some modem exponents of his social doctrinessuggest that his ideas are not original and say that he might havetaken them from Ibn Sin$ or Ibn Khaldiin. However, a totalist view ofhis framework of thought shows that this is an unwamted assertion ...